Noções de saúde e espiritualidade presente no clássico chinês HUÁNG DÌ NÈI JING (Livro do Imperador Amarelo) - Beltrão, Izabelita Cirne (2017)
The Medicine developed previously in China has a complex structure to explain the human being constitution, through a correlations mechanism with fundamental laws that govern the cosmos. These fundamentals has their theoretical, practical and philosophical aspects and are concentrated in the Huáng Dì Nèi Jing Sù Wèn Líng Shu Chinese Classical, the oldest Chinese medicine text that came to us, was compiled by the "doctor" Daoísta Wáng Bing in the dynasty Táng (762 d. C.). Chinese Medicine, because it is globalizing, it has its understanding compromised, having its philosophical, theoretical and practical aspects considered separately, what happens when we use it for only symptomatic cure purposes. Because of this classic importance, we aim to understand the health notions presented in this Chinese classic, by examining the extent to which the available translations published in Brazil differ in the treatment they give to this theme and the intrinsic reason that has with Daoism in its original content.